2021
DOI: 10.1017/s0030605319001431
|View full text |Cite
|
Sign up to set email alerts
|

Marginal farmers carry the burden of damage caused by Asian elephants Elephas maximus in Bardiya National Park, Nepal

Abstract: In areas where farmland borders protected areas, wildlife may be attracted to crops and cause substantial financial damage for farmers. Elephants, in particular, can destroy a year's harvest in a single night, and can also cause damage to buildings and other farm structures. Few studies have examined whether damage caused by wild elephants increases social inequalities in farmer communities. We interviewed settlement leaders and subsistence rice farmers living in the buffer zone of Bardiya National Park, Nepal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The Bardia National Park (BNP) is the largest national park in the plains (Terai), characterized by high human population density (GoN, 2022). The population of mega‐species, including tigers and one‐horned rhinoceros, has increased (DNPWC & DFSC, 2018; Heinen et al, 2019), resulting in increased human‐wildlife conflict incidences (Heinen et al, 2019; Prins et al, 2022; Shahi et al, 2021). Although there are few studies undertaken in BNP focusing on attitudes (Allendorf et al, 2007; Baral & Heinen, 2007), conservation benefits (Thapa Karki, 2013), and resource dependency on the park (Thapa & Hubacek, 2011), little is known what socio‐demographic factors explain their attitudes toward the PA.…”
Section: Introductionmentioning
confidence: 99%
“…The Bardia National Park (BNP) is the largest national park in the plains (Terai), characterized by high human population density (GoN, 2022). The population of mega‐species, including tigers and one‐horned rhinoceros, has increased (DNPWC & DFSC, 2018; Heinen et al, 2019), resulting in increased human‐wildlife conflict incidences (Heinen et al, 2019; Prins et al, 2022; Shahi et al, 2021). Although there are few studies undertaken in BNP focusing on attitudes (Allendorf et al, 2007; Baral & Heinen, 2007), conservation benefits (Thapa Karki, 2013), and resource dependency on the park (Thapa & Hubacek, 2011), little is known what socio‐demographic factors explain their attitudes toward the PA.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies in Bardia National park, Nepal also have shown that the farmers in the boundary had small landholding and had a relatively higher cost of damage (Prins et al 2021). This results in a situation where community/cooperative-based protection measures do not work effectively because of varying interests and cooperation among farmers thus undermining or eliminating more effective or e cient crop protection methods that need a cooperative approach from the villagers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some farmers with very small holdings may nd it more remunerative to work as laborers than to cultivate small and unproductive patches of land. The disparity in the economic status of farmers on the periphery adds another dimension to the crop protection scenario (Prins et al 2021). Poor or marginal farmers are likely to abandon their elds thus creating gaps in the peripheral protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, elephants in locations with high human disturbance levels move in larger groups, move faster, show increased nocturnal activity (Graham et al, 2009; Songhurst et al, 2016) and approach villages for forage (Cook et al, 2015). Damage caused by elephants is of particular conservation interest because where it occurs it is often both frequent and severe (Osborn & Parker, 2003; Prins et al, 2022). In the villages of south-west Gabon, for example, encroachment into villages and crop damage by elephants have remained the major drivers of negative human–wildlife interactions over the last decade and are amongst the main causes of the impoverishment of local people (Fairet, 2012; Hill, 2017; Terada et al, 2021).…”
Section: Introductionmentioning
confidence: 99%